Stay at Home and Teach: A Comparative Study of Psychosocial Risks Between Spain and Mexico During the Pandemic - Prado-Gascó, Vicente; Gómez-Domínguez, María T.; Soto-Rubio, Ana; Díaz-Rodríguez, Luis; Navarro-Mateu, Diego (Frontiers in Psychology, 2020)
Context The emergency situation caused by COVID-19 has affected different facets of society. Although much of the attention is focused on the health sector, other sectors such as education have also experienced profound transformations and impacts. This sector is usually highly affected by psychosocial risks, and this could be aggravated during the current health emergency. Psychosocial risks may cause health problems, lack of motivation and a decrease of effectiveness at work, which in turn affects the quality of teaching. Despite their importance, there are hardly any studies that analyse psychosocial risks of non-university teachers during a health emergency such as that caused by COVID-19. Objectives The aim of this study was to analyse the perception of COVID-19 and the psychosocial risks of non-university teachers comparing Spain and Mexico during the state of alarm caused by COVID-19. Methods Data were collected from 421 non-university teachers (80.2% women; 56% from Mexico, 43.7% from Spain) aged 24 to 60 (M=39.32, SD=10.21) via a self-completed questionnaire during the pandemic from March to April 2020. Results Data analysis suggest that inequity is the most important risk, followed by work overload. Teachers appear to be moderately satisfied with the information on COVID-19 and the measures taken, while their satisfaction with the available resources is lower. When comparing the two countries, significant differences can be observed in every risk considered except for Social Support, with lower levels in Mexican teachers compared to Spanish ones. In the case of the perception of the COVID-19 and its impact, the perception in general of levels of information, measures and resources is better among Mexican teachers than among Spanish ones, who present higher scores of the impact of the health emergency. Conclusions The results underline the importance of professional’s perception of resources during a health emergency, which could prevent to some extent burnout and possible alterations associated with it. The measures taken by the responsible entities and the provision of information do not only affect teachers directly, but also indirectly by making them more vulnerable to psychosocial risks that could affect their health and professional performance, thus affecting students as well.